Problematika Yang Dihadapi Pendeta Dalam Pelayanan di Masa Pandemi Covid-19 - Sarah Priska Toding; Simon Simon (Sekolah Tinggi Teologi Nusantara, 2021)
This study specifically details what problems priests experience in ministry during the Covid-19 Pandemic. The current ongoing outbreak certainly causes the complexity of probematics caused by the corona virus. Using qualitative methods with literary and phenoological approaches in presenting this topic. The review of this article outlines that the corona virus causes problems with the drastic decrease in the mobility rate of mankind. Concrete from the decline in the mobility of the global community including aspects of work, aspects of education, aspects of the character, aspects in carrying out religious rituals. This outbreak also causes problems in the psychological side that is characterized by the ease of stressed people and the lack of empathy towards others. This difficult condition is also experienced by pastors, as a result of which makes it more difficult for them to carry out ecclesiastical ministry activities. As for the probematics that were surpassed by the priest during this pandemic, limited access and problems making pastoral care visits to sick congregations, especially in hospitals. Although pastors are faced with this reality, church ministry and ministry to the congregation must be pursued. Keywords: Covid-19 Pandemic, Pastors, Church Services ABSTRAK Kajian ini menyororoti secara spesifik problematika apa yang dialami oleh para pendeta dalam pelayanan di masa Pandemi Covid-19. Wabah yang sedang berlangsung saat ini tentu menyebabkan kompleksitasnya probematika yang diakibatkan oleh virus corona. Dengan menggunakan metode kualitatif dengan pendekatan literatur dan fenomologis dalam memaparkan topik ini. Ulasan pada artikel ini menguraikan bahwa virus corona mengakibatkan problematika dengan menurunnya tingkat mobilitas umat manusia secara drastis. Kongkrit dari penurunan mobilitas masyarakat global diantaranya aspek dalam bekerja, aspek pendidikan, aspek berelasi, aspek dalam menjalankan ritual keagaman. Wabah ini juga menyebabkan problematika dalam sisi psikologi yang ditandai mudahnya orang stress serta makin minimnya sikap empati terhadap sesama. Kondisi yang serba sulit ini turut dialami oleh para pendeta, akibatnya makin menyulitkan mereka melakukan aktivitas pelayanan gerejawi. Adapun probematika yang dilami oleh pendeta dimasa pandemi ini, akses yang terbatas serta problem melakukan kunjungan pelayanan pastoral pada jemaat yang sakit khususnya di rumah sakit. Walau para pendeta diperhadapkan pada realita ini, pelayanan gereja dan pelayanan kepada jemaat harus diupayakan tetap berjalan. Kata Kunci: Pandemi Covid-19, Pendeta, Pelayanan Gereja